Condition of outdoor sculptures in ASEAN sculpture garden Kuala Lumpur : a conservation study / Nora Sofia Mohamed Yuran - Mohamed Yuran, Nora Sofia (2006)
The purpose of this study is to describe the condition of outdoor sculptures in ASEAN Sculpture Garden. This objective is to find out the details of the conditions of outdoor sculptures in ASEAN Sculpture Garden and identify any visible damages and to determine the condition in order to make recommendations for the conservation plan. The research questions are: How is the condition of outdoor sculptures in ASEAN Sculpture Garden? Is there any visible damage? What are the rates of condition of outdoor sculptures in ASEAN Sculpture Garden? Is it good, poor or at risk condition? Are there any recommendations for the conservation plan? Data is collected from condition survey through on-site documentation "and condition survey. All population of outdoor sculptures in ASEAN Sculpture Garden is selected as study samples. Six works of outdoor sculptures in ASEAN Sculpture Garden are assessed in order to identify the current conditions. The works are The Gate of Harmony, Progress, The ASEAN Dance, Growth, Barong-Barong, and Towards Peace. Data is analyzed in chronologically into six categories. Each category contains a series of tables with descriptive texts and pictures. The results of condition of outdoor sculptures in ASEAN Sculpture Garden indicate that The Gate of Harmony, Progress, The ASEAN Dance, Growth, and Towards Peace in fair condition and not at risk. However, Barong-Barong is identified as in poor condition and at risk. Recommendations for conservation plan are made for ways to stabilize the conditions of the outdoor sculptures in ASEAN Sculpture Garden. These included detailed assessment, urgent treatment, and substantial research on the deterioration of the objects. This study's conclusions indicate that the forms of damage such as water collect, cracks surfaces, broken glasses or biological attack resulting the outdoor sculptures in fair and poor conditions after being exposed to almost all of the factors that cause damage and deterioration for over 15 years. Most of the sculpture structures forms and the materials used are bound to rust, to collect water and breakable glasses over a period of time. Therefore, the best way to protect the lives of outdoor sculptures is to give awareness to artist to use the correct materials and use appropriate structure forms in the creation of outdoor sculpture in order to prevent further deterioration.